Outcomes with image-based interstitial brachytherapy for vaginal cancer. Issue 3 (September 2016) - Manuel, Matthias M.; Cho, Linda P.; Catalano, Paul J.; Damato, Antonio L.; Miyamoto, David T.; Tempany, Clare M.; Schmidt, Ehud J.; Viswanathan, Akila N.
Abstract: Purpose: To compare clinical outcomes of image-based versus non-image-based interstitial brachytherapy (IBBT) for vaginal cancer. Methods and materials: Of 72 patients with vaginal cancer treated with brachytherapy (BT), 47 had image guidance (CT = 31, MRI = 16) and 25 did not. Kaplan–Meier (KM) estimates were generated for any recurrence, local control (LC), disease-free interval (DFI), and overall survival (OS) and Cox models were used to assess prognostic factors. Results: Median age was 66 and median follow-up time was 24 months. Median cumulative EQD2 dose was 80.8 Gy in the non-IBBT group and 77 Gy in the IBBT group. For non-IBBT versus IBBT, the 2-year KM LC was 71% vs. 93% ( p  = 0.03); DFI was 54% vs. 86% ( p  = 0.04); and OS 52% vs. 82% ( p  = 0.35). On multivariate analysis, IBBT was associated with better DFI (HR 0.24, 95% CI 0.07–0.73). Having any 2 or more of chemotherapy, high-dose-rate (HDR) BT or IBBT (temporally correlated variables) significantly reduced risk of relapse (HR = 0.33, 95% CI = 0.13–0.83), compared to having none of these factors. Conclusion: Over time, the use of chemotherapy, HDR, and IBBT has increased in vaginal cancer. The combination of these factors resulted in the highest rates of disease control. Image-guided brachytherapy for vaginal cancer patients maximizes disease control.